Effect of adding zeolite and probiotics to the diet on the growth and digestion of Awassi lambs - الرز, محمد; عادل جمول ,; وليد الرحمون,; ياسر العمر , (Latakia University Journal -Biological Sciences Series, 2024)
Sheep breeding projects depend on nutrition, the availability of feed materials, their nutritional value, and the extent of benefit from them. Therefore, the use of antibiotics has spread as food additives that work to improve the efficiency of food conversion and raise the productivity of agricultural animals while maintaining the physiological and health condition of the animal, and in view of the great fears that prevail in the world regarding the use of antibiotics. In animal nutrition and its effects on human and animal health, therefore, there has recently been a discussion of alternatives to it. Therefore, attention has turned to probiotics, of which yeast is one of the types, which improve the productive standards of animals, such as weight gain, digestion coefficients, and milk production, while maintaining the natural physiological state of animals. Also, recent attention has been directed to Taking advantage of some elements available in nature, such as clay stones, of which zeolite is one type, and whose use in feeding rations led to an improvement in the production standards of animals and did not have negative effects on the health of the animals. Therefore, the importance of this research was that it works to provide unconventional food additives that are available at acceptable prices. It has no negative effects on the health of animals.